Radon and Lung Cancer - Gaskin, Janet (Université d'Ottawa / University of Ottawa, 2019)
Background: Lung cancer was the fifth leading cause of mortality globally in 2010, and the leading cause of cancer mortality in Canada, representing 26% of all cancer deaths for both men and women in 2017. Radon is a very modifiable environmental exposure that is the second most important cause of lung cancer. Objectives: The objectives of this thesis are to quantify the lung cancer burden associated with residential radon and to identify the most cost effective mitigation options to reduce residential radon in Canada. Methods: The global burden of lung cancer mortality attributable to radon in 2012 was estimated from the 66 countries for which a representative national radon survey was available, using several different models for excess relative risk (ERR) of lung cancer from radon studies. Cost-utility analyses are conducted for 20 practical radon interventions scenarios to reduce residential radon exposures in new and existing housing in Canada, each province/territory and 17 census metropolitan areas. A societal perspective and a lifetime horizon are adopted. A Markov cohort model and a discrete event simulation are used to model residents by household, based on a period-life table analysis, at a discount rate of 1.5%. Results: The estimates of the global median PAR were consistent, ranging from 16.5% to 13.6% for the three ERR models based on miners, and the mean estimates of PAR for Canada ranged from 16.3% to 14.6%. It is very cost effective to install radon preventive measures in new construction compared to no radon control in all regions across Canada. At a radon mitigation threshold of 100 Bq/m3, the sequential analysis recommends the combination of the activation of preventive measures in new housing with the mitigation of existing housing at current testing and mitigation rates for cost effectiveness thresholds between 51,889 and 92,072 $/QALY for Canada, between 27,558 and 85,965 $/QALY for Manitoba, and between 15,801 and 36,547 $/QALY for the Yukon. The discounted ICER for screening and mitigation of existing housing at current rates relative to no radon control measures is 62,451 (66,421) $/QALY using a Markov cohort model (discrete event simulation model) for mitigation of housing above a threshold of 200 Bq/m3, and is 58,866 (59,556) $/QALY using a Markov cohort model (discrete event simulation model) for mitigation of housing above a threshold of 100 Bq/m3. Conclusions: Cost effective residential radon interventions should be implemented across Canada to reduce exposures to this very modifiable cause of lung cancer and to help reduce the increasing lung cancer burden in an ageing Canadian population.
Keywords: Radon; Lung cancer; Cost-Utility analysis; Population health